2004
DOI: 10.1007/s11240-004-4540-5
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of alfalfa with a bacterial fusion gene, Mannheimia haemolytica A1 leukotoxin50-gfp: Response with Agrobacterium tumefaciens strains LBA4404 and C58

Abstract: Alfalfa transformed with a portion of the leukotoxin gene from Mannheimia haemolytica was produced to test the feasibility of developing an edible vaccine capable of protecting cattle from pneumonic pasteurellosis. Leukotoxin (Lkt), has been identified as an important protective antigen of M. haemolytica, and a fragment, Lkt50, was shown to produce toxin-neutralizing antibodies in rabbits. The construct chosen for introduction into alfalfa carried lkt50 fused to a green fluorescent protein reporter gene, mgfp5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Однако работы носили поисковый характер -частота трансформации была небольшой, генетические конструкции (вектора) содержали только селективные или репортерные гены. В настоящее вре-мя, несмотря на обилие публикаций по успешной агро-бактериальной трансформации люцерны (Rosellini et al, 2007;Zhang et al, 2010), все еще имеются трудности, связанные с необходимостью индивидуального подбора условий трансформации в зависимости от генотипа, типа экспланта, штамма агробактерии и вектора для транс-формации (Nincovic et al, 2004;Ziauddin et al, 2004). В литературе описаны следующие основные подходы, применяемые при агробактериальной трансформа-ции: инкубация эксплантов в суспензии агробактерии (Faragova et al, 2011;Liu et al, 2013;Zhang et al, 2010) в условиях вакуумной инфильтрации; культивирование на газоне агробактерии (Trinh et al, 1998); в редких слу-чаях -трансформация in planta (Weeks et al, 2008).…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…Однако работы носили поисковый характер -частота трансформации была небольшой, генетические конструкции (вектора) содержали только селективные или репортерные гены. В настоящее вре-мя, несмотря на обилие публикаций по успешной агро-бактериальной трансформации люцерны (Rosellini et al, 2007;Zhang et al, 2010), все еще имеются трудности, связанные с необходимостью индивидуального подбора условий трансформации в зависимости от генотипа, типа экспланта, штамма агробактерии и вектора для транс-формации (Nincovic et al, 2004;Ziauddin et al, 2004). В литературе описаны следующие основные подходы, применяемые при агробактериальной трансформа-ции: инкубация эксплантов в суспензии агробактерии (Faragova et al, 2011;Liu et al, 2013;Zhang et al, 2010) в условиях вакуумной инфильтрации; культивирование на газоне агробактерии (Trinh et al, 1998); в редких слу-чаях -трансформация in planta (Weeks et al, 2008).…”
Section: результаты и обсуждениеunclassified
“…В литературе описаны следующие основные подходы, применяемые при агробактериальной трансформа-ции: инкубация эксплантов в суспензии агробактерии (Faragova et al, 2011;Liu et al, 2013;Zhang et al, 2010) в условиях вакуумной инфильтрации; культивирование на газоне агробактерии (Trinh et al, 1998); в редких слу-чаях -трансформация in planta (Weeks et al, 2008). В качестве эксплантов обычно используют эмбриоиды, каллусы, семядоли, гипокотили, листовые диски, а так-же проростки и семена (Nincovic et al, 2004;Ziauddin et al, 2004;Uzelac et al, 2007). В нашей работе были использованы две основные схемы агробактериальной трансформации.…”
Section: результаты и обсуждениеunclassified
“…In vitro leaf-disc transformations were performed as described in Ziauddin et al (2004). Transformations Fig.…”
Section: Plant Transformation and Embryogenesismentioning
confidence: 99%
“…Although transformation efficiencies of 27-47% are routinely obtained with kanamycin-based selection (Ziauddin et al 2004), reported transformation efficiencies for pat/bar selection are in the range of 3.5-16% (D'Halluin et al 1990;Tabe et al 1995;Barbulova et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has been frequently used to produce industrial proteins such as enzymes (Austin et al 1995;Ullah et al 2002), biodegradable polymer (Saruul et al 2002), or insect proteinase inhibitor (Thomas et al 1994). Recently, alfalfa has also been used to express pharmaceuticals proteins (Dus Santos et al 2002;Ziauddin et al 2005). This legume species was chosen for the production of C5-1, a monoclonal antibody (Khoudi et al 1999).…”
Section: Introductionmentioning
confidence: 99%